Weight Training or Be a Burden - Christiana, Metta; Muhaimin, Ahmad; Puspitasari, Wahyu; Kartika, Shinta Eka (Edumedia Solution, 2025)
Sarcopenia is a condition characterized by decreased muscle mass and strength, characterized by a decline in physical ability, beginning around the age of 40 due to the aging process. A significant number of residents of Bangetayu Wetan Village, 5,694 people, are over 40 years old and experience various physical complaints such as knee pain, back pain, fatigue, muscle and joint stiffness, physical weakness, obesity, high blood sugar, blood pressure, cholesterol, and so on.Residents of Bangetayu Wetan Village are unaware that one of the risk factors for these complaints is muscle mass loss, or sarcopenia. One effective way to prevent and manage sarcopenia is through regular weight training.This community service activity aims to provide knowledge about sarcopenia and how to manage it through weight training. The expected benefit of this activity is that residents of Bangetayu Wetan Village over 40 will be able to identify and address their health problems.